A SOCIOLINGUISTIC CONTEXT ANALYSIS OF SPEECH ACTS ILLOCUTIONARY FORCES - Haryanto Haryanto (Tarbawi : Jurnal Pendidikan Islam, 2013)
ABSTRACTThis paper is aimed at analyzing the components of situational context of ??speech event?, which are grouped in word ??SPEAKING?? by Dell Hymes (1972). It is summed up from an acronym of the components like: Setting, Scene, Participants, Ends, Act Sequence, Key Instrumentality, Norms, and Genres. It is a Case Study among the Activist Students of in Campus.Keywords : Speech Acts, Illocutionary Forces, locution, Illocution, Perlocution ABSTRAKPaper ini bertujuan untuk menganalisa komponen-komponen konteks situasi ??kejadian tutur?, yang terangkum dalam kata ??SPEAKING?? oleh Dell Hymes (1972). Singkatan kata ini merupakan rangkuman dari komponen-komponen seperti: Latar, Layar, Peserta, Hasil, Rangkaian Tutur, Instrumen Kunci, Norma-norma, dan Jenis Tutur. Tulisan ini adalah sebuah studi kasus diantara para aktivis mahasiswa di kampus.Kata-kata Kunci : Tindak Tutur, Dorongan Lokusi, Illokusi, Perlokusi